Macrophage migration inhibitory factor promotes resistance to MEK blockade in KRAS mutant colorectal cancer cells - Seul‐Ki Cheon (Molecular Oncology, 2018)
Although MEK blockade has been highlighted as a promising antitumor drug, it has poor clinical efficacy in KRAS mutant colorectal cancer (CRC). Several feedback systems have been described in which inhibition of one intracellular pathway leads to activation of a parallel signaling pathway, thereby decreasing the effectiveness of single‐MEK targeted therapies. Here, we investigated a bypass mechanism of resistance to MEK inhibition in KRAS CRC. We found that KRAS mutant CRC cells with refametinib, MEK inhibitor, induced MIF secretion and resulted in activation of STAT3 and MAPK. MIF knockdown by siRNA restored sensitivity to refametinib in KRAS mutant cells. In addition, combination with refametinib and 4‐IPP, a MIF inhibitor, effectively reduced the activity of STAT3 and MAPK, more than single‐agent treatment. As a result, combined therapy was found to exhibit a synergistic growth inhibitory effect against refametinib‐resistant cells by inhibition of MIF activation. These results reveal that MIF‐induced STAT3 and MAPK activation evoked an intrinsic resistance to refametinib. Our results provide the basis for a rational combination strategy against KRAS mutant colorectal cancers, predicated on the understanding of cross talk between the MEK and MIF pathways.